Novelties in Grammitis Sw. and StenoGrammitis Labiak (Polypodiaceae) from Costa Rica, Colombia, and Venezuela - Alexander F. Rojas-Alvarado (Actualidades Biológicas, 2013)
Four new species of Grammitis Sw. (G. angustissima A. Rojas, G. roraimensis A. Rojas, G. spathulata A. Rojas and G. undulata A. Rojas) and one new species of StenoGrammitis Labiak (S. grammitoides A. Rojas) are described here. The first species is known only from the Colombian Andes and is characterized by a very narrow blade; the second is known only from the Roraima Mountains in Venezuela, and is the largest species with a long ascending rhizome and a branched blackish blade ribbon; the third species is similar to G. marginella (Sw.) Sw. in spathulate blade with rounded apex, but has sessile fronds and a glabrous blade; the fourth species is also known from the Colombian Andes, and it is similar to G. angustissima in its narrow blade, but has undulate margins and a narrower blackish marginal ribbon; the StenoGrammitis species is endemic to Cocos Island, Costa Rica, and is characterized by clathrate rhizome scales, an entire blade, and discontinuous sori that are oblique at the costa.